Giant cell tumour of bone with late presentation: review of treatment and outcome. - Ng, E.S.; Saw, A.; Sengupta, S.; Nazarina, A.R.; Path, M. (2002)
Even in an advanced stage of disease, good clinical outcomes can be achieved with adequate excision and appropriate reconstruction. For lesions around the knee, autologous rotational grafting is a good alternative method of reconstruction.